ISLAMIC EDUCATION THOUGHTS OF KH. AHMAD DAHLAN AT THE YAMISA ISLAMIC BOARDING SCHOOL IN 1968 - Alimuddin Ali (Indonesian Journal of Islamic History and Culture, 2023)
Islamic education is an educational system based on the Qur'an and Sunnah. Kh. Ahmad Dahlan in his thoughts on Islamic education based on the Qur'an and Sunnah. This must be accompanied by other sciences or what is commonly referred to as other general sciences in order to create individuals who are rich in knowledge outside of religious knowledge. The education system at the Yamisa Islamic Boarding School, despite applying the teachings of the Qodariyah Naqsabandiyah order. But in practice in line with Kh. Ahmad Dahlan in which the Yamisa Islamic Boarding School teaches its students about religion and includes other knowledge so that the students have broad knowledge. The methodology used in making this article is to use historical research methods which consist of several stages, namely heuristics, criticism, interpretation and historiography. The research method in this article uses the historical method. The first source collection was to find information and collect data from a book entitled Kh. Ahmad Dahlan (1868-1923), Rattan the Kiai: The Life Story of Mama Uyeh. Sources from the internet such as e-books, journals entitled understanding of education, Islamic Education Thought Perspective Kh. Ahmad Dahlan (1869-1923) and Kh. Hasyim Asy'ari 1871-1947(M): Comparative study in the concept of reforming Islamic education in Indonesia. and other articles such as the thesis entitled Islamic Education Thought According to Kh. Ahmad Dahlan. As well as interviews conducted with Mr. Heri Haris Mawardi as the administrator of the Yamisa boarding school. Islamic Education KH. Ahmad Dahlan at Yamisa Islamic Boarding School, although in practice there are differences in his flow because of NU and Muhammadiyah. However, in terms of the education system, it is not much different, because the thought of Islamic education at the Yamisa pesantren also applies the same thing as KH. Ahmad Dahlan in his education system. Namely, Yamisa Islamic Boarding School also implements a non-formal education system so that the education system can keep up with the times with openness to general knowledge so that students gain knowledge related to religion and the public.